Potential use of bamboo in the phytoremediation in of heavy metals: A review - Liang, Zhiwei; Kovács, Gergő Péter; Gyuricza, Csaba; Neményi, András (Acta Agraria Debreceniensis, 2022)
There are many literature sources focusing on the phytoremediation of woody plants, but there are only few dealing with the phytoremediation of bamboo plants. Phytoremediation technology has the advantages of little disturbance to the environment and low remediation cost. Bamboo mainly exists in tropical and subtropical regions. As an energy plant, bamboo has a fast growth cycle, large biomass, simple cultivation, high economic efficiency, and convenient harvesting, which highlights the advantages of bamboo in phytoremediation. In addition, bamboo plants have good tolerance and uptake ability to heavy metals and have high application potential and development value in uptaking heavy metal contaminated soil. However, due to climate, temperature and other reasons, bamboo cannot be widely planted in most countries. Research status of remediation of heavy metal contaminated soil by bamboo plants is summarized. The feasibility of its application in heavy metal contaminated soil is discussed in this paper. Aiming at the shortcomings of existing research, bamboo plants have a prospect in the field of plant phytoremediation for the future.